LOCAL DEMOCRACY AND FORMS OF DIRECT CITIZEN PARTICIPATION IN GOVERNMENT - Radojević, Mijodrag (Serbian political thought, 2023)
The subject of this paper is the institutions of direct democracy at the local level in Serbia, with the aim of analyzing valid solutions (de lege lata) and improving the legal framework (de lege ferenda). The author starts from the thesis that local democracy is an ambiguous and imprecise term. In a broader sense, it represents the right of citizens to participate in government at the local level. In a narrower sense, this term is used as a synonym for local self-government (decentralization) and direct participation of citizens in government. On the other hand, tradition, socio-economic assumptions, legal (normative) framework and political environment are factors that influence local democracy. Apart from the election of local government representatives (representative local democracy), the basic institutional channels of local democracy are forms of direct citizen participation of citizens in decision-making, such as referendum and people's initiative. The application of institutions of direct democracy can be one of the indicators of the level of development of local self-government and local democracy.In the Republic of Serbia, institutional mechanisms for direct citizen participation in local self-government have been created, such as referendums, citizens' initiatives, and assembly of citizens (збор). In addition, citizens have the right to petition and publicly criticize the authorities, the right to be heard on the authorities’ intentions and the right to be informed about and monitor the work of the authorities. The local referendum is enshrined in  the Constitution and other institutions are regulated by legal provisions. The quality of these regulations improved after the adoption of the new Law on Referendums and People's Initiative (2021). However, in local self-government units, the scope of these institutions of direct democracy is very limited low. The practice of direct local democracy is very poor, although there is a long tradition of struggle for local self-government in the 19th century. Such a situation is a consequence of the party state that multiplies the centralized way of decision-making, which is manifested in limited participation of citizens in political processes, increasing distrust in political institutions and ineffective control of the authorities in local self-government units. The crisis of democracy also manifests itself in the fact that citizens are less and less interested in public policy. Based on empirical data, comparative experiences and legal standards, the author believes that the solution lies in reviving the application of direct democracy at the local level.
Keywords: local self-government, direct democracy, referendum, people's initiative, assembly of citizens (збор), Law on Local Self-Government, electronic voting.